Ecological Literacy of Students Based on Local Wisdom Handep in Developing Environmental Care Character of Grade IX Students at SMP Negeri 4 Palangka Raya - Sihotang, Sesilia Stefania; Mustika, Maryam (Universitas Tanjungpura, 2024)
In facing the 4.0 era which is marked by rapid technological developments and climate change, environmental sustainability has become a crucial issue that requires serious attention. This research aims to foster an environmentally caring character through understanding ecoliteracy based on local Handep wisdom, a practice of mutual cooperation in Kalimantan society. The Action Research Method with a qualitative approach was used to involve class IX students, teachers and parents at SMP Negeri 4 Palangka Raya. Ecoliteracy materials were developed by utilizing local Handep wisdom, focusing on understanding, knowledge, attitudes and behavior based on ecology. The research results show that Handep-based ecoliteracy material can increase students' awareness about caring for the environment and good resource management. Apart from that, this material can also increase students' interest in developing environmentally caring character. Applying ecoliteracy with a local wisdom approach can help students overcome environmental problems in a more effective way. The process of increasing understanding and application of knowledge through this method displays positive results in forming environmentally caring character at the secondary school level. Therefore, ecoliteracy materials based on local wisdom can be used as an effective alternative for developing environmentally caring character, good resource management, and overcoming environmental challenges in schools, making a positive contribution to increasing the environmental awareness of the younger generation in this technological era.